ANALISIS STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA: PERSPEKTIF HUMAN INVESTMENT MANAGEMENT (HIM), HUMAN RESOURCE MANAGEMENT (HRM) DAN HUMAN CAPITAL MANAGEMENT (HCM) - Sumartan, Sumartan; Akob, Muh; Jumady, Edy; Alam, Syamsu; Syahruddin, Herman (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
Human resource development (HRD) has become a strategic factor in enhancing organizational competitiveness and sustainability in the era of global competition. However, partial approaches to HR management often hinder the optimal utilization of individual and organizational potential. This study aims to analyze HRD strategies from three main perspectives: Human Resource Management (HRM), Human Capital Management (HCM), and Human Investment Management (HIM). The research employs a literature review method with a descriptive qualitative approach, examining various scholarly sources related to the concepts and practices of HRD. The findings indicate that HRM focuses on operational aspects such as recruitment and training; HCM emphasizes the management of competencies as strategic assets; while HIM views human resources as long-term investments requiring sustainable development planning. The integration of these three perspectives offers a more holistic approach to designing effective HRD strategies. This study concludes that a balanced emphasis on operational efficiency, human capital optimization, and investment orientation in HR management is essential to achieving long-term organizational goals.